The effectiveness test of sunscreen cream with raw materials of coconut oil and active ingredients of Soursop (Annona Muricata L) leaf and Bay (Eugenia Polyantha Wight) leaf ethanol extracts - Eni Widiyati; Devi Ratnawati; Dyah Fitriani; Lesta Nurul Jayanti; Nadia Arum Pangestu (RAFFLESIA JOURNAL OF NATURAL AND APPLIED SCIENCES, 2022)
The purpose of this study was to determine the effectiveness of cream made  of coconut oil as a raw  material and the active ingredients of soursop leaf ethanol extract  and bay leaf ethanol extract as sunscreens. The cream was made by mixing the hot (700C) water phase (glycerin, distilled water, methyl paraben, and triethanolamine = TEA) and the hot (700C) oil phase (s tearic acid, coconut oil, cetyl alcohol, propyl paraben, andlanolin). After the cream was formed, the active ingredients of soursop leaf ethanol extract and bay leaf ethanol  extract were added. A cream without an active ingredient was also made as a comparison.  The produced cream was determined to have ultraviolet (UV) radiation absorption by using a UV spectrophotometer. The resulting absorbance value was used to calculate the value of the sun protection factor (SPF) using the Mansur equation. The results showed that creams without active ingredients had the lowest SPF values. With an SPF of 3.048, the cream with 2% active ingredients and 2.5% bay leaf extract was labeled as a low-performance sunscreen cream